From the history of art as a current possibility of humanism in Julius von Schlosser and Giulio Carlo Argan (2014)
The complex world of thought and sensitivity in the sphere of contemporary art has entailed the revision and exclusion of disciplines aimed at providing a model to explain and conceptualize reality. Art history, as one such discipline, has had many of its